Recent advances in cowpea breeding - Singh, B.; Chambliss, O.; Sharma, B. (1997)
Cowpea is an important grain legume throughout the tropics and subtropics, covering Asia, Africa, and Central and South America, as well as parts of southern Europe and the United States of America. The use patterns, seed preferences, and cropping systems vary from region to region. Insect pests, diseases, nematodes, parasitic weeds, and drought are major production constraints. Early maturity is preferred everywhere so that cowpeas can be grown in the niches of cereal-based cropping systems, but medium- and late-maturing varieties, with and without photosensitivity, are also required in some regions, to suit the prevalent cropping systems and meet grain and fodder needs. Considerable progress has been made during the past decade in cowpea breeding, and a range of varieties has been developed, combining diverse plant type and maturity with resistance to several diseases, insect pests, and parasitic weeds. Improved varieties have also been developed for grain and fodder and for intercropping with maize, cassava, yam, millet, and sorghum for the benefit of smallholder farmers who practice intercropping and use little or no inputs.